PELATIHAN DENGAN METODE PERSEPTORSHIP UNTUK MENINGKATKAN EMPOWERMENT DAN KOMPETENSI KARYAWAN BAGIAN PELAYANAN KLINIK SARI MEDIKA - Kadarningsih, Ana; Dian Prawitasari (Jurnal Padamu Negeri, 2025)
A community service activity themed training with a preceptorship model to develop the competency of Sari Medika Clinic employees in Ambarawa, Central Java was attended by 41 service department employees. The service department consists of six divisions: midwives, nurses, medical records, pharmacy, laboratory, and cashiers. Participants consisted of 36 women and 5 men. This training aims to develop competency and increase empowerment of human resources effectively. The training method uses the preceptorship method which is conducted offline or face-to-face for one day. The training results showed that participants' knowledge increased after being given competency development training with the preceptorship model. This increase was indicated by the post-test results of 48.78% in the good category compared to the pre-test results of 24.39% in the good category. The training results also showed that Sari Medika Clinic service department employees were able to act as preceptors (role models) to guide other employees in developing their potential and competency. Competency development training activities with the preceptorship model were prepared to prepare committed and competent employees as professionals in their respective divisions. Committed and competent employees will create empowerment effectively so that increased employee productivity will be achieved.